2005
DOI: 10.1002/art.21405
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic outcomes of four different treatment strategies in patients with early rheumatoid arthritis (the BeSt study): A randomized, controlled trial

Abstract: Objective. Several treatment strategies have proven value in the amelioration of rheumatoid arthritis (RA), but the optimal strategy for preventing long-term joint damage and functional decline is unclear. We undertook this study to compare clinical and radiographic outcomes of 4 different treatment strategies, with intense monitoring in all patients.Methods. In a multicenter, randomized clinical trial, 508 patients were allocated to 1 of 4 treatment strategies: sequential disease-modifying antirheumatic drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
869
4
48

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,279 publications
(980 citation statements)
references
References 29 publications
45
869
4
48
Order By: Relevance
“…Our analysis showed that the effect of a TNF inhibitor plus methotrexate was significantly superior to combination DMARD treatment during the first 6 months, but this difference almost disappeared after 12 months, and especially after 18/24 months (no outcomes differed). Furthermore, in 3 studies using an initial course of steroids (3,4,14,15), there was no difference between the 2 treatment principles at any time (Figures 2-5 and Supplementary Figures 1-3, available in the online version of this article at http://onlinelibrary.wiley. com/doi/10.1002/acr.22618/abstract).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis showed that the effect of a TNF inhibitor plus methotrexate was significantly superior to combination DMARD treatment during the first 6 months, but this difference almost disappeared after 12 months, and especially after 18/24 months (no outcomes differed). Furthermore, in 3 studies using an initial course of steroids (3,4,14,15), there was no difference between the 2 treatment principles at any time (Figures 2-5 and Supplementary Figures 1-3, available in the online version of this article at http://onlinelibrary.wiley. com/doi/10.1002/acr.22618/abstract).…”
Section: Discussionmentioning
confidence: 99%
“…A recent indirect comparison network meta-analysis indicated that the effects of combination treatments with and without biologic agents might have similar properties to reduce radiographic joint destruction (2). Until recently, only 1 randomized controlled trial (RCT) directly supported this hypothesis (3,4). The 4 most sold drugs in the world with regard to sales (but not defined daily doses) are biologic agents primarily indicated for RA (adalimumab, infliximab, rituximab, and etanercept).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BeSt Study was a multicenter, randomized, single-blind clinical trial (Dutch trial registry; trial numbers NTR262 and NTR265) set up to evaluate 4 dynamic treatment strategies in 508 patients with recentonset active RA (1987 American College of Rheumatology classification criteria) (9). Details of the study have been previously described (10). All patients gave written informed consent for the original study, and after separate approval from the medical ethics committees of the participating centers, also gave written informed consent for the additional questionnaire concerning the present topic.…”
Section: Methodsmentioning
confidence: 99%
“…57 This conclusion is supported by a 2010 Cochrane systematic review that emphasized lack of evidence of a statistically significant advantage for initial combination therapy using MTX and other conventional DMARDs over monotherapy with MTX. 58 A [59][60][61][62][63][64] The results of these studies suggest that the combination of MTX with a TNF inhibitor or CTLA-4:Ig (abatacept) has greater efficacy than MTX monotherapy insofar as both clinical and radiographic outcomes are concerned.…”
Section: Treatment Approach Initial Treatment Approachmentioning
confidence: 99%